A new trap for collecting aquatic and semi‐aquatic insects from madicolous habitats. Issue 6 (1st July 2015) - Shimabukuro, Erika M.; Pepinelli, Mateus; Perbiche‐Neves, Gilmar; Trivinho‐Strixino, Susana
Abstract: A new trap is described for capturing adult insects (especially Chironomidae) from madicolous habitats in mountainous environments. The trap is light enough to be carried and is easy and inexpensive to build, being constructed of mosquito netting fabric (no‐see‐um mesh size), galvanised wire, a plastic bottle, a plastic conduit and nylon clamps. Seventy‐one traps deployed along an altitudinal gradient on three different mountains (altitude 0–2700 m above sea level) captured c . 1400 adult insects, representing 20 higher taxa (i.e. families or orders) of insects.